2018
DOI: 10.1186/s12885-018-4717-7
|View full text |Cite
|
Sign up to set email alerts
|

Low serum gastrin associated with ER+ breast cancer development via inactivation of CCKBR/ERK/P65 signaling

Abstract: BackgroundGastrin is an important gastrointestinal hormone produced primarily by G-cells in the antrum of the stomach. It normally regulates gastric acid secretion and is implicated in a number of human disease states, but how its function affects breast cancer (BC) development is not documented. The current study investigated the suppressive effects of gastrin on BC and its underlying mechanisms.MethodsSerum levels of gastrin were measured by enzyme-linked immunosorbent assay (ELISA) and correlation between g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 54 publications
0
6
0
Order By: Relevance
“…However, it might also inhibit tumor growth. Therefore, the concrete role of gastrin in tumorigenesis might be organand/or molecular subtype-dependent manner (19,20). Further studies are warranted to elucidate the role of SEMA5B and GAST in HNSCC tumorigenesis.…”
Section: Discussionmentioning
confidence: 99%
“…However, it might also inhibit tumor growth. Therefore, the concrete role of gastrin in tumorigenesis might be organand/or molecular subtype-dependent manner (19,20). Further studies are warranted to elucidate the role of SEMA5B and GAST in HNSCC tumorigenesis.…”
Section: Discussionmentioning
confidence: 99%
“…The activated ERK was reported to promote IkBa phosphorylation and subsequently induce NF-kB (Rel) nuclear translocation in glioblastoma cells and murine colitis (39,40). The cholecystokinin B receptor (CCKBR) in breast cancer cells could activate the ERK/P65 pathway (41). After ERK was inhibited, P65 activity was found to be reduced in MKN28 cells (42).…”
Section: Discussionmentioning
confidence: 99%
“…PDE4B is mainly present in immune and epithelial cells and has a role modulating inflammation and epithelial integrity 96 while CCKBR encodes a G-protein coupled receptor for gastrin and cholecystokinin. Even though CCKBR has not been targeted for treatment of endometriosis, a recent study has demonstrated that reduction of gastrin is associated with inactivation of CCKBR/ERK/P65 signalling in estrogen receptor positive breast cancer cells, and lower expression of gastrin and CCKBR was correlated to worse prognosis in breast cancer 97 . Therefore, the involvement of gastrin and CCKBR in estrogen metabolism may implicate this gene as a potential drug target for endometriosis.…”
Section: Discussionmentioning
confidence: 99%